The Implementation of Early Intervention Services of Southern Special Education Center under Special Education Bureau - Jindewha, Amira; Wannapairo, Suntaree (Journal for Developing the Social and Community, 2025)
Background and Aims: The purpose of this study was to examine the implementation of student support services at the Southern Special Education Centers under the Office of the Special Education Administration, comparing the operations according to gender, age, educational qualification, and work experience, as well as to explore strategies for development. Methodology: The study employed a mixed-methods approach. The sample consisted of 254 teachers from the Southern Special Education Centers, selected through simple random sampling. Data were collected using a 5-point Likert scale questionnaire and interviews. The data were analyzed using percentages, means, standard deviations, t-tests, one-way analysis of variance (ANOVA), and pairwise comparisons using the LSD method. Results: Overall, the implementation of student support services was rated at the highest level () = 4.5262, S.D. = 0.4655). The area with the highest mean score was the development of family-specific support plans and individualized education plans, followed by the organization of appropriate activities. The area with the lowest mean score was student progress assessment. Comparisons of the implementation results by gender, age, and educational qualification revealed no statistically significant differences; however, some differences were observed when grouped by work experience, specifically in screening and referral, basic skills assessment, and supervision, monitoring, and evaluation significantly different at the .05 level. Development strategies identified from interviews with administrators included fostering collaboration among teachers, parents, and multidisciplinary professionals; systematic data collection; planning and developing individualized education plans; implementing appropriate activities; and continuous supervision, monitoring, and evaluation. Conclusion: The findings indicate that the Southern Special Education Centers operate effectively; however, emphasis should be placed on improving the student progress assessment system and follow-up mechanisms in order to enhance service quality and adequately respond to the needs of students in a sustainable manner.